The Quarterly Journal of Economics Volume 129 November 2014 Issue 4 - Front Cover (Quarterly Journal of Economics, 2014)
Journal Article The Quarterly Journal of Economics Volume 129 November 2014 Issue 4 - Front Cover Get access The Quarterly Journal of Economics, Volume 129, Issue 4, November 2014, Page i1, https://doi.org/10.1093/qje/qjt052 Published: 16 December 2014